Mineralogy, petrology and geochemistry of the lower and lower critical zones, Northwestern Bushveld Complex - Teigler, Bernd (Rhodes University, Faculty of Science, Department of Geology, 1991)
This study of the lower part of the Rustenburg Layered Suite in the Western Bushveld Complex is based mainly on drill core samples from three localities, which are approximately 130 km apart. The NG-sequence, situated in the northwestern sector of the complex (Union Section, R.P.M.) extends from the floor of the complex to the base of the upper Critical Zone. The sequence is ca. 1800 m thick and it comprises mainly ultramafic cumulates, namely pyroxenites, olivine pyroxenites, harzburgites and dunites. Norites and anorthos ites are present only in minor proportion. Within the upper half of the NG-sequence ten prominent chromitite layers are correlated with the LGI MG4-interval. Correlation is also established between published sequences and the two other sequences studied, located 8 km and 55 km, respectively, east of Rustenburg. Whole-rock chemical data (major and trace elements), microprobe and Sr isotope data are presented. Petrographic studies provide modal analyses and measurements of grain size. All petrographic, mineralogical and other geochemical data point to an origin of the cumulates of the NG-sequence by crystallization from liquids of the U-type lineage and derivatives thereof. No evidence is found for the involvement of parental liquids with a distinctly different composition or crystallization order (A-liquids). However, subtle compositional variations of the parental liquids are evident in slight changes of the Cr content in orthopyroxene or in variations of Sr isotope ratio. The NG-sequence is characterized by intervals with reversed fractionation trends caused by repeated influxes of pristine magma (during periods of high magmatic activity) resulting in a high degree of rejuvenation. These intervals are overlain by others with a normal fractionation trend, interpreted as cumulates formed in periods with low or no magmatic activity, in which fractional crystallization controlled bulk composition of the evolving liquid. The Lower Zone in the NG-sequence is dominated by a progressive shift towards more primitive compositions, while in the Critical Zone fractionation was the major operating process in the magma chamber. However, during deposition of the pyroxenitic lower Critical Zone several replenishment events occurred, during which fresh Cr-rich magma was emplaced. Massive chromitite layers were deposited after mixing between the newly emplaced magma and the resident residual liquid shifted bulk compositions into the primary field of chrome-spinel. Cumulus plagioclase crystallized after bulk composition of the residual liquid was driven to the orthopyroxene plagioclase cotectic by continued fractional crystallization; this occurred once in the Lower Zone, yielding a single, thin norite layer, and again in the upper Critical Zone of the NG-sequence. A facies model is proposed based on the stratigraphic and compositional variations along strike in the Western Bushveld Complex. This model explains the variations by means of the position of the sequence with regard to a feeder system. The olivine- and orthopyroxene-rich, but plagioclase-poor NG-sequence represents the proximal facies, while the SF-sequence (poor in ferromagnesian phases, but plagioclase-rich) is developed as a distal facies, close to the Brits graben.
Keywords: Mineralogy -- South Africa -- North-Western Transvaal; Petrology -- South Africa -- North-Western Transvaal; Geochemistry -- South Africa -- North-Western Transvaal